2019
DOI: 10.3389/fnagi.2018.00429
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fucoidan on Cellular Oxidative Stress and the CatD-Bax Signaling Axis in MN9D Cells Damaged by 1-Methyl-4-Phenypyridinium

Abstract: Background: The purpose of this study was to investigate the impact of fucoidan (FUC) on the oxidative stress response and lysosomal apoptotic pathways in the Parkinson disease (PD) cell model.Methods: The Dopaminergic nerve precursor cell line(MN9D) cells that served as a PD model in this study underwent damage induced by 100 μM 1-methyl-4-phenyl pyridine (MPP+). Cell viability was assessed after FUC treatment and intracellular SOD GSH was measured via immunofluorescence assay. Cellular changes in cathepsin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Three fucoidan extracts from Sargassum crassifolium attenuated H 2 O 2 -induced cytotoxicity in rat pheochromocytoma PC-12 cells [ 205 ]. In the MPP + PD model, fucoidan attenuated cytotoxicity in a dopaminergic neuronal precursor cell line (MN9D) [ 183 , 186 ] by protecting lysosomes, reducing the expression of light chain 3-II (LC3-II), inhibiting the expression of cathepsin D (CatD)-Bax and the OS response [ 186 ]. Fucoidan of Sargassum hemiphyllum attenuated 6-hydroxydopamine-induced apoptosis in SH-SY5Y cells [ 206 ].…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%
“…Three fucoidan extracts from Sargassum crassifolium attenuated H 2 O 2 -induced cytotoxicity in rat pheochromocytoma PC-12 cells [ 205 ]. In the MPP + PD model, fucoidan attenuated cytotoxicity in a dopaminergic neuronal precursor cell line (MN9D) [ 183 , 186 ] by protecting lysosomes, reducing the expression of light chain 3-II (LC3-II), inhibiting the expression of cathepsin D (CatD)-Bax and the OS response [ 186 ]. Fucoidan of Sargassum hemiphyllum attenuated 6-hydroxydopamine-induced apoptosis in SH-SY5Y cells [ 206 ].…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%
“…Various models of Parkinson’s disease treated with fucoidans have shown encouraging data [95,96]. While the mechanism behind these results is unclear, the recent findings on microbiome connections with Parkinson’s disease and many other neurological conditions point to a potential effect on gut microbiota [97].…”
Section: Neuroprotectionmentioning
confidence: 99%
“…Newer reports about the molecular pathways involved in fucoidan neuroprotective effects on dopaminergic nerve precursor cells (MN9D) treated with 1-methyl-4-phenyl pyridine (MPP + ) suggest its involvement in increasing superoxide dismutase (SOD) activity and reduced glutathione (GSH) concentration and decreasing the apoptosis levels by downregulation of Bax expression [13].…”
Section: Fucoidan and Neurodegenerationmentioning
confidence: 99%
“…The above characteristics and effects are described in further detail in this review in correlation with pre-clinical and translation research for treatment of mental disorders, and brain damage due to disease and injury. Indeed, there is substantial evidence regarding its protective and beneficial actions in the central nervous system (CNS), both at whole organ and cellular levels, which is a plausible starting point for developing novel therapies for severe neurodegenerative and neurocognitive disorders such as Alzheimer Disease (AD), Parkinson Disease (PD), and others [13,14]. Furthermore, another line of research confirmed the beneficial influence of fucoidan in preserving cellular integrity and inhibition of fibrosis in drug-induced liver injury and hepatocellular carcinoma [15,16].…”
Section: Introductionmentioning
confidence: 99%